Intra-operative neurophysiological prediction of upper trunk recovery in obstetric brachial plexus palsy with neuroma in continuity - Chin, K.F.; Misra, V.P.; Sicuri, G.M.; Fox, M.; Sinisi, M. (The British Editorial Society of Bone & Joint Surgery, 2013)
We investigated the predictive value of intra-operative neurophysiological investigations in obstetric brachial plexus injuries. Between January 2005 and June 2011 a total of 32 infants of 206 referred to our unit underwent exploration of the plexus, including neurolysis. The findings from intra-operative electromyography, sensory evoked potentials across the lesion and gross muscular response to stimulation were evaluated. A total of 22 infants underwent neurolysis alone and ten had microsurgical reconstruction. Of the former, one was lost to follow-up, one had glenoplasty and three had subsequent nerve reconstructions. Of the remaining 17 infants with neurolysis, 13 (76%) achieved a modified Mallet score > 13 at a mean age of 3.5 years (0.75 to 6.25). Subluxation or dislocation of the shoulder is a major confounding factor. The positive predictive value and sensitivity of the intra-operative EMG for C5 were 100% and 85.7%, respectively, in infants without concurrent shoulder pathology. The positive and negative predictive values, sensitivity and specificity of the three investigations combined were 77%, 100%, 100% and 57%, respectively. In all, 20 infants underwent neurolysis alone for C6 and three had reconstruction. All of the former and one of the latter achieved biceps function of Raimondi grade 5. The positive and negative predictive values, sensitivity and specificity of electromyography for C6 were 65%, 71%, 87% and 42%, respectively. Our method is effective in evaluating the prognosis of C5 lesion.Neurolysis is preferred for C6 lesions.